PERANCANGAN DASHBOARD DAN PREDIKSI PENJUALAN UNTUK TOKO NAGAMASYURMART - Halim, Nelson (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The impact of Covid-19 has affected the economy individually, households, micro, small, medium and large companies, even affecting the country's economy with a scale of local, national and even global coverage. Although on the one hand the economy is weakening, on the other hand, the economy is also experiencing improvement, namely in the electronic commerce or e-commerce sector. Consumer needs for various kinds of products that can prevent and protect themselves from the transmission of Covid-19, such as masks, have increased. The increase in various types of masks from various manufacturers makes it difficult for Nagamasyurmart stores to monitor sales and make decisions in predicting future product sales. The purpose of designing this dashboard is to make it easier for store owners to find out sales information in visual form and make decisions easier. Sales data used in designing this dashboard is sales data from Nagamasyurmart Stores. The method used in designing this dashboard is the prototype method, while the prediction method used is the linear regression method. The results obtained are a sales dashboard with sales predictions to make it easier for store owners to make decisions for further sales.